2009
DOI: 10.1002/gps.2328
|View full text |Cite
|
Sign up to set email alerts
|

Support/services among family caregivers of persons with dementia—perceived importance and services received

Abstract: The results from this study suggest that there is almost no difference between groups of caregivers experiencing higher and lower NI regarding their perception of what are important types of support/services. The caregivers rated different types of support/services within the areas of information, relief and counselling as very important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 20 publications
2
21
0
Order By: Relevance
“…The strong negative effect on the families caring for the member with BD, with no stronger positive value being gained or feelings being supported, can be compared with results by Alwin et al . (2010) showing higher negative effect scores for these families (mean 14.9) than those of family caregivers of persons with dementia (mean 13.0).…”
Section: Discussionmentioning
confidence: 83%
“…The strong negative effect on the families caring for the member with BD, with no stronger positive value being gained or feelings being supported, can be compared with results by Alwin et al . (2010) showing higher negative effect scores for these families (mean 14.9) than those of family caregivers of persons with dementia (mean 13.0).…”
Section: Discussionmentioning
confidence: 83%
“…This behavioral approach identified specific concerns and tailored strategies to individual needs, consistent with the empirical literature (Gallagher‐Thompson and Coon, ) and meeting practice guidelines for dementia care (Vasse et al ., ). Carers report such types of support as important and preferred (Alwin et al ., ). Participants reported viewing segments and complying with between‐session assignments.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of 34 interventions showed that the family caregivers to persons with dementia appraised their own coping skills as improved by the intervention 20. In a study where the aim was to examine the family caregivers’ apprehension regarding what type of support they found important, the results revealed that the family caregivers rated support and service within the areas of information, relief, and counseling as highly important 21. This corresponds with a study where family caregivers communicated the need for better knowledge of the disease, as well as education on ways to handle cognitive and different behavioral disorders 22.…”
Section: Discussionmentioning
confidence: 99%